Energy-Saving Design of Building Envelope Based on Multiparameter Optimization. (10th December 2019) - Gan, Weinan; Cao, Yunzhong; Jiang, Wen; Li, Liangqiang; Li, Xiaolin
Abstract : The contradiction between the indoor environment and building energy consumption has been controversial. The design of building envelope involves many parameters such as window size and exterior wall material. These parameters have significant influence on building energy-saving design and indoor environment. In this paper, nondominant sorting genetic algorithm-II (NSGA-II) is utilized to calculate winter heat consumption, indoor total lighting energy consumption, and thermal comfort. The Pareto method is used to select the compromise solution and effective value of each building parameter. Different from other studies, we add more architectural design variables into the model calculation, which can bring architects more detailed energy-saving design content.